Study of Antioxidant and Anti Hyperglycemia of some Active Chemicals Compounds Isolated for Iraqi Arnebia hispidissima medicinal plant - Khalawi, Anwar Qasim; Alsaadi, Jamal Harbi Hussein; Alsaadi, Jamal Harbi Hussein (International Journal of Psychosocial Rehabilitation, 2020)
Arnebia hispidissima is a medicinal plant belonging to family boraginaceae, which has Anti- inflammatory, Antibacterial, wound-healing and the Antifungal properties. General extracts were prepared from Iraqi Arnebia hispidissima . They are hot aqueous , cold aqueous and ethylacetate extracts. Moreover, preliminary qualitative tests were carried out for all extracts prepared, qualitative analysis the phytochemical arnebia hispidissima extracts showed the presence of glycosides, terpenoids, saponin, alkaloids, phenols, carbohydrates, flavonoids and tannins, than had estimated total quantitative of phenol and flavonoids, where the highest yield of phenol (0.0175mg/ml) in the cold aqueous extract .While the results showed the highest yield of flavonoids(0.1037mg/ml) in the hot aqueous extract And in light of testing antioxidant effectiveness by inhibiting the DPPH scavenging activity, Reducing power and Fe3+ Reducing, it showed that the studied plant exhibits an antioxidant activity with different levels in all plant extracts. The highest DPPH scavenging activity , Fe3+ Reducing and Reducing power activity were found in hot aqueous extract of A. hispidissima at a concentration of (100µg/ml) with a (91.22%) inhibition ratio. the highest ferric reducing power (75.11mg/ml) at concentration(5 mg/ml) and highest chelating activity of ferrous ion at Concentration (5mg/ml) was (79.15mg/ml) Moreover, study of hypoglycemic action in blood glucose levels in alloxan induced diabetic mice to know activity these extracts in decreasing blood glucose levels in these mice . the results indicated that all extracts showed good decreasing in glucose level. Hot aqueous extract from A. hispidissima showed high activity to decrease blood glucose than others extract ,where significant decreasing (P<0.05) was found at second and sixth hrs. and high significant decreasing (P<0.05) at twenty four hrs. The present study concluded that A. hispidissima extracts have antioxidant and antihyperglycemic activity as it lower blood-glucose level in diabetic mice.